Predicting entrepreneurship intention among Malay university accounting students in Malaysia - Mohd Ariff, Arifatul Husna; Bidin, Zainol; Sharif, Zakiyah; Ahmad, Adura (Universiti Tun Abdul Razak, 2010)
The Malaysian government strongly promotes entrepreneurship as a career choice among students.However, many students do not turn out to be entrepreneurs after their graduation, especially Malays.The students’ behaviour and decision to get involved in entrepreneurship can be further explained by their intention.Therefore, this study identifies factors that influence students’ intention to become an entrepreneur based on the model of the Theory of Planned Behaviour (TPB).A sample of 121 final year Malay accounting students completed questionnaires from Universiti Malaya and Universiti Utara Malaysia, consisting of 18 items measuring attitude towards entrepreneurship, subjective norm, perceived behavioural control, and intention to be an entrepreneur was compiled. The findings of the study show that all three factors significantly influence students’ intention to become entrepreneurs.Out of these three factors, perceived behavioural control emerged as the strongest factor that had a strong influence on intention.This implies that the TPB model is capable of predicting students’ intention towards entrepreneurship, and further explain the students’ decision to become an entrepreneur in the future.The implications to the theory and policy makers are discussed further in this study.